Assessment Analysis of Bank Soundness Level using RGEC Approach in Banking Companies Listed on The IDX in 2019–2021 - Anjani, Alivia Saktia; Indriani, Eni; Kartikasari, Nungki (Jurnal Manajemen, 2023)
This study aims to analyze the soundness level of a bank using the Risk Profile, Good Corporate Governance, and Capital (RGEC) method in accordance with the Financial Authority Regulation Number 4/POJK.03/2016 in all banking sectors listed on the Indonesia Stock Exchange in 2019-2021. This research is descriptive research with a quantitative approach. The data used in this study is secondary data derived from the financial statements of the banking sector. The results showed that in 2019 there were nine banks that received a composite rating of one or very healthy, eighteen banks received a composite rating of two or healthy, ten banks received a composite rating of three or quite healthy, 5 banks received a composite rating of 4 or less healthy, and one bank that gets a rating of five or unhealthy. Then in 2020 there were nine banks that received a composite rating of one or very healthy, twenty one banks received a composite rating of two or healthy, six banks received a composite rating of three or quite healthy, one bank received a composite rating of five or unhealthy. In 2021, thirteen banks will receive a composite rating of one or very healthy, nineteen banks will receive a composite rating of two or healthy, four banks will receive a composite rating of three or quite healthy, six banks will receive a composite rating of four less healthy, one bank will receive a composite rating of five or not healthy. Nineteen banks will receive a composite rating of two or healthy, four banks will receive a composite rating of three or quite healthy, six banks will receive a composite rating of four unhealthy, and one bank will receive a composite rating of five or not healthy. Keywords: Bank Performance, IDX listed bank, RGEC